Holey reduced graphene oxide inducing sensitivity enhanced detection nanoplatform for cadmium ions based on glutathione-gold nanocluster - Mo, Fengye; Ma, Zhangyan; Wu, Tengteng; Liu, Meiling; Zhang, Youyu; Li, Haitao; Yao, Shouzhuo (Sensors and actuators. B, Chemical, 2019)
[Display omitted] •A new fluorescence nanoplatform for sensitive detection of Cd2+ was developed based on AuNCs and HRGO.•The FL of AuCNs were quenched by HRGO owing to the FRET between them.•FL was recovered when adding Cd2+ in the system owing to the formation of Cd-GSH complex.•The HRGO-AuNCs FL-OFF-ON nanoplatform has larger FL quench efficiency than that of GO.•Improved detection sensitivity for Cd2+ was obtained compared with using GO-AuNCs or AuNCs nanoplatform. Heavy metal contamination is a widely focused topic in environmental analysis and health care in recent years. Herein, a new fluorescence (FL) nanoplatform for sensitive detection of Cd2+ was developed based on AuNCs and holey reduced graphene oxide (HRGO). HRGO was obtained by hydrothermal method using graphene oxide (GO) as the precursor, H2O2 as an etchant and ascorbic acid (AA) as a reducing agent. GSH-AuNCs were synthesized by using glutathione (GSH) as the template and reducing agent. The FL of AuCNs were quenched by HRGO, which may result from fluorescence resonance energy transfer (FRET) between AuNCs and HRGO and then the FL was recovered when adding Cd2+ in the system owing to the formation of Cd-GSH complex. In the presence of the holey, inter-crossing and open structure of the HRGO, the HRGO-AuNCs FL-OFF-ON nanoplatform has larger FL quench efficiency than that of GO. At the same time, the nanoplatform can further provide a more convenient environment for Cd2+ detection with improved detection sensitivity compared with those in the presence of GO or direct detection of Cd2+ using AuNCs. At the optimized concentration of HRGO, the fluorescence intensity of HRGO-AuNCs increased with the concentration of Cd2+ and the linear range was 0.1-100 μM with the detection limit of 42.0 nM. Moreover, the nanoplatform can be used for Cd2+ in real samples with good accuracy and excellent recovery. Therefore, the attempt of HRGO in fluorescence nanoplatform may be expanded to other optical sensing areas or medicine delivery and has great prospective.